Bulkamid® injection in men: Cadaver study of operative technique and putative mechanism of action. (November 2022) - Toia, Bogdan; O'Connor, Eabhann; Greenwell, Tamsin J; Ockrim, Jeremy L; Solomon, Eskinder
Objective: Post-prostatectomy incontinence (PPI) is relatively common and of variable degree. Treatment of small-volume persistent PPI with a male sling or an artificial urinary sphincter is overly invasive, and the concept of intraurethral injection is very appealing in this situation. Bulkamid ® is a nanoparticulate polyacrylamide and water polymer gel which is being used successfully in female stress urinary incontinence. We assessed the feasibility and effects of a four-point intraurethral technique on maximum urethral pressure (MUP) in male cadavers. Methods: Urethral pressure profile (UPP) was measured twice on two male fresh-frozen cadaver models before and after a four-point injection of 2 mL of Bulkamid ® intraurethrally at the level of the sphincter in 0.5 mL aliquots using a 21Ch cystoscope with a 12° telescope and a 23G needle. Results: A clear UPP trace was recordable in both cadavers. The mean MUP at baseline was 38 cm H2 O, and the mean MUP following Bulkamid ® intraurethral injection increased to 55 cm H2 O. Conclusions: Bulkamid ® intraurethral injection in male cadavers is a simple technique that increases MUP. This increase in MUP may allow for treatment of low-volume PPI in men following prostate cancer treatment and warrants further study in the clinical situation. Level of evidence: Level 4.